Relationship between trait anger and rejection sensitivity: the moderating role of the group (inmates and non-inmates). Issue 6 (2nd November 2021) - Bodecka, Marta; Grala, Krzysztof; Szymczak, Karol; Zajenkowska, Anna; Rajchert, Joanna; Kostrzewska, Dagmara; Lawrence, Claire
ABSTRACT: The current study tested the differential relationship between Trait Anger (TA), Sensitivity to Provocation (SP) and Rejection Sensitivity (RS) among inmates convicted of violent offenses (N = 123) and community dwelling adults (N = 118). It was hypothesized that inmates would have higher RS and that RS would be more strongly related to TA. We also investigated whether SP would have additional impact on RS, over and above the effect of TA. There were no differences between inmates and non-inmates in RS when other variables were not controlled for. Trait Anger predicted RS in both groups, but the relationship between TA and RS was stronger in inmates. However, when Sensitivity to Provocation was included in the model, SP predicted Rejection Sensitivity and the relation between TA and RS only remained positive in the inmate group. The current study extends the knowledge on RS, demonstrates the importance of TA for this sensitivity, it is also a pioneering work that investigates RS in a group of individuals convicted for violent crimes.